CORROSION STUDY OF SS316L IN ENVIRONMENT SULPHUR ACID USING WEIGHT LOSS METHOD - Ayu Arwati; Samsul Sianipar (SINERGI, 2018)
Application of SS 316 metal is commonly used as a building material in the chemical industry. This material is commonly used because it has good mechanical properties, corrosion resistant, but in reality, the SS 316 L metal can corrosive its acid environment, making it easy to solve the problem. corrosion. Therefore, this study is aimed to study SS316L corrosion level in H2SO4 acid by using weight loss method with 1 day, 3 days and 5 days immersion in H2SO4 environment with concentration 0,1 M, 0,3 M and 0,5 M The results showed that the corrosion rate increased with increasing concentration of H2SO4 and yield up to 5 days with average corrosion rate (CR) 2.729078 x 10-6 mpy. Morphological damage SS 316 L is demonstrated by SEM (Electron Microscope Scanning) there is a pitting corrosion on the metal surface